Ex-situ conservation of threatened forest tree species for sustainable use of forest genetic resources in Bangladesh (Journal of Biodiversity Conservation and Bioresource Management, 2018)
The present study was carried out to advance towards the conserving threatened forest tree species of Bangladesh under ex-situ conservation system. Four thousand plants of forty eight threatened forest tree species were conserved at three areas, namely Institute of Forestry and Environmental Sciences, Chittagong University; Radar Unit of Bangladesh Air Force, Cox‟s Bazar; and the Keochia research station of Bangladesh Forest Research Institute. The average 90-95% plants survived in each conservation site and the maximum average plant height was recorded as 4.0m after two years of plantation. It will provide a wider buffer for the protection of the forest gene resources.J. Biodivers. Conserv. Bioresour. Manag. 2018, 4(2): 89-98